PERAN INTERNATIONAL COMMITTE OF THE RED CROSS UNTUK MELINDUNGI KORBAN AGRESI DI PALESTINA BERDASARKAN KONVENSI JENEWA 1949 DAN PROTOKOL TAMBAHAN I 1997 - Hafni Zanna Dewi; Chairul Bariah; Arif Arif (Journal of USU International Law, 2017)
ABSTRACTWar is the most thorniest issues in the world, reflect on the conflict which broke out into a cold war in Palestine made the world should be more sensitive to see that with the establishment of written rules regarding the Regulations on Human Rights are still not enough to cope with casualties falling, for this the ICRC stands, where the ICRC as a neutral institution that handles humanitarian issues from time to time are increasingly required by the international community. The ICRC has a major role in efforts to provide assistance and relief to victims of armed conflict, whether occurring in the territory of a country or between countries. This is evidenced also by the mandate given to the ICRC by the international community. ICRC has also shaped by the 1949 Geneva Conventions and Additional Protocol I and Additional Protocol II as a principal instrument in carrying out the functions and role in helping humanitarian work in conflict areas. The method used is a normative legal research methods with data collection procedures are the main source material of a legal nature normative law. Data were acquired and processed in a normative legal research is secondary data derived from literature sources. The research result of this paper shows that the authority of the ICRC in carrying out the functions and role in providing humanitarian assistance has been listed in the 1949 Geneva Conventions and their Additional Protocols I & II 1997, the Statutes of the Movement of Red Cross and Red Crescent International, and two protocols in addition, the process of its formulation supported actively by the ICRC. Going forward, the ICRC managed to deliver real action and the ICRC required role in dealing with victims of war. Keywords: International Committee of the Red Cross, the 1949 Geneva Convention,Additional Protocol I and II of 1977, the Israeli- Palestinian conflict.